Something unforeseeable happened? Natural rate theory and economic crisis - Ronald Schettkat (Intereconomics, 2010)
Natural rate theory' - the application of the efficient market hypothesis to labour markets - has guided economic policy since the 1970s and laid the foundations for the design of major European institutions in the 1990s. Unfettered markets were declared to be stable, and consequently public policies and regulations were regarded as distortions. This led to a division of labour in which central banks were responsible only for price stability, governments for labour market reforms and unions for low wages. The European discussion focused almost exclusively on labour market reforms to reduce unemployment. Against the background of the recent dramatic drop in economic activity, this paper confronts natural rate theory with actual economic trends and argues that the predictions of the theory hardly fit the facts.
Keywords: 330